(3GdeSDhdjI GdGLJeGYjI h GdGNdGbjI (B:s (3JhLg VQhQj aj Xd GdCReGJ (B/s - (3aJjMI, BjJ GhbGSjs; (3eNJGQ QMeGfj, McjeIs; (3bjOhe, SgGes ((3GdLRGFQ(B: s (3OGQ GdCLjGd GdQbej(B, s, 2024)
(3gOaJ GdOQGSI Edi EHQGR QDjI fXQjI Mhd JaYjd EHYGO GdeSDhdjI GdGLJeGYjI ddJYGed eY GdCReGJ hOhQ UjGZI GSJQGJjLjGJ GdeSDhdjI GdGLJeGYjI dehGLgI GdCReGJ, aGdCReI gj MGdI MQLI heaGLFI ddOhd hGdeLJeY JDKQ Ydi GSJbQGQ GdeDSSGJ hCaQGO GdeLJeY(B. (3dPdc CUHMJ dHQGeL GdeSDhdjI GdGLJeGYjI OhQ aYGd aj ehGLgI GdCReGJ hGdMO ef JOGYjGJgG Ydi GdaQO hGdeLJeY ef CLd JQSjN GdeDSSGJ ecGfJgG GdGLJeGYjI hGdCNdGbjI aj GdeLJeY(B. s
(3eQGLY U(B.453-454s
Keywords: (3GdCReGJ GdGbJUGOjIs; (3GdJfejI GdeSJOjeIs; (3GdeSDhdjI GdGLJeGYjIs